Tissue composition, quality traits and fatty acid profile of longissimus muscle of lambs fed increasing levels of crude glycerin - C. M. Cunha; A. R. M. Fernandes; T. C. Cornélio; H. A. Ricardo; L. G. C. Alves; L. O. Seno; J. C. S. Osório (Boletim de Indústria Animal, 2016)
The objective of this study was to evaluate the tissue composition, quality traits and fatty acid profile of longissimus muscle of lambs fed increasing levels of crude glycerin. Twenty-four intact male lambs were allocated in a completely randomized design with four treatments and six replicates. The treatments consisted of the replacement of corn with 0, 2.5, 5.0 and 7.5% crude glycerin (dry matter basis) in the diet. The animals were slaughtered when they reached a body condition score of 2.5 to 3.0. After cooling the carcasses, the meat was removed for the determination of tissue composition and longissimus muscle for the evaluation of quality characteristics. The different crude glycerin levels did not affect tissue weight or yield, or the qualitative characteristics of longissimus muscle. An increasing linear effect was observed for ether extract. There was a quadratic effect on C17:0 fatty acids, and C18:1 n-9c and C18:3 n-3 fatty acids decreased linearly. A quadratic effect was observed for total unsaturated fatty acids and a linear decreasing effect for n-3 fatty acids. The unsaturated:saturated fatty acid ratio decreased linearly and there was an increasing linear effect on the n6:n3 ratio. Crude glycerin can replace corn without compromising tissue composition and quality traits of longissimus muscle. The inclusion of up to 7.5% crude glycerin (dry matter basis) in the diet for Pantaneiro lambs improves the nutritional aspects of fat.